Effective-Range-Expansion Study of Near Threshold Heavy-Flavor Resonances - Rui Gao; Zhi-Hui Guo; Xian-Wei Kang; J. A. Oller (Advances in High Energy Physics)
In this work, we study the resonances near the thresholds of the open heavy-flavor hadrons using the effective-range-expansion method. The unitarity, analyticity, and compositeness coefficient are also taken into account in our theoretical formalism. We consider the Zc(3900), X(4020), χc1(4140), ψ(4260), and ψ(4660). The scattering lengths and effective ranges from the relevant elastic S-wave scattering amplitudes are determined. Tentative discussions on the inner structures of the aforementioned resonances are given.